Implementasi Nilai-Nilai Pendidikan Multikultural di Perguruan Tinggi (Studi Kasus di Prodi PGSD Universitas PGRI Palembang Sumatera Selatan) - Miftahul Husni (Institut Agama Islam Negeri (IAIN) Curup, 2019)
The Republic of Indonesia is a country that has a very heterogeneous and pluralistic population, starting from religion, ethnicity, culture and also language. So the motto of this country is